A wolf from Gravettian site Pavlov I, Czech Republic: Approach to skull pathology - Sazelová, Sandra; Lawler, Dennis; Hladilová, Šárka; Boriová, Soňa; Šáliová, Soňa; Janoušek, Tomáš; Perri, Angela; Hublin, Jean-Jacques; Svoboda, Jiří (International journal of paleopathology, 2020)
OBJECTIVE: Describe pathological features on internal and external aspects of the skull of an ancient grey wolf. MATERIALS: Wolf remains that were found at the southwestern settlement Area A of Gravettian site Pavlov I. METHODS: Visual observation and description; microcomputed tomography; porosity and fragmentation indices for internal and external skull features; histological section of the fourth upper premolar tooth. RESULTS: Dorsally, the sagittal crest revealed bone healing and remodeling. The sagittal lesion differential diagnosis was blunt trauma with or without fracture. Ventrally, otic region pathology included severe proliferation and lysis (osteomyelitis). The pathology was not resolvable among differential (microbial) causes of osteomyelitis, although other potential etiologies were ruled out. CONCLUSIONS: Probable first report of otic region osteomyelitis in an ancient grey wolf. SIGNIFICANCE: The proximity of the wolf remains to human-related findings, and presence of red ochre and shells, suggest human involvement in the burial. LIMITATIONS: This is a single specimen with differential diagnoses that were not resolvable to a single definitive diagnosis. SUGGESTIONS FOR FURTHER RESEARCH: Further investigation of the possible anthropological significance of the burial circumstances.
Keywords: Wolves; Burial; paleopatologie; Archeozoology; vlci; Skull; archeologie; Grey wolf; pohřeb; zvířata; dějiny starověku; Osteomyelitis; Differential diagnosis; History, Ancient; Archaeology; Mid-Upper Paleolithic; Czech Republic; osteomyelitida; Animals; lebka; Česká republika; Paleopathology